Two-color, two-photon uncaging of glutamate and GABA - Kantevari, Srinivas (2009)
We have developed a method for bimodal control of neuronal membrane potential with subcellular resolution using optically independent two-photon uncaging of glutamate at 720 nm and GABA at 830 nm. Two-color, two-photon uncaging allowed action potentials to be fired and blocked with the two wavelengths of light and may enable optically independent control of many other symbiotic chemical messenger pairs.